Тhe historiography of development problems of the national school educational literature in the 20s – 80s of the twentieth century (Pedagogy of Higher and Secondary Education, 2013)
Josan O. E. Тhe historiography of development problems of the national school educational literature in the 20s – 80s of the twentieth century.Author has analyzed the historiography of the problem of school educational literature in 1921 – 1989 years: works of scientists, teachers, educational leaders, special historiographical researches on theory of educational literature, lexicography and Bibliology, historical and pedagogical researches published from 1921 to 2012.
Keywords: scientific sources; historiography of the problem; school educational literature; theory of educational literature; lexicography; Bibliology